The Religious Education Teacher as a Guide in Fostering Identity, Celebrating Diversity and Building Community - Roebben, Bert (REVER: Revista de Estudos da Religião, 2015)
This contribution is situated in the European discourse on the role of the teacher of religious/worldview education in schools. Based on the assumption that every child and youngster has the right to deal with existential questions in a safe and solid learning environment, the author focuses on the specific role of the teacher to enhance religious/worldview competence and identity development in the students. Within the idea of professionalism three roles can be discerned: the teacher as a guide in fostering identity, celebrating diversity and building community. These professional roles have a counterpart in the spiritual disposition of the teacher. This argument is developed through a specific reading of the medieval German mystical theologian Meister Eckhart. Surprising thoughts on who the teacher is and what he should do (and eventually not do) are evoked and discussed.